(untitled) (Research, Society and Development, 2020)
Information and Communication Technology (ICT) is the nomenclature used to refer to communication mediated by technological instruments that provide access and understanding of school and scientific knowledge of the present century. The general objective of this research aims to know the perception of biologist educators about the use of ICT in the teaching process of the curricular subjects of the Biological Sciences Degree course, offered by the Campus of the Federal Institute of Maranhão (IFMA) Municipality of Barreirinhas - MA. As for the methodological procedures, the strategy consisted of an analytical and hermeneutic reading of articles that dealt with the theme in focus; application of questionnaires with the seven Biology professors of the IFMA - Campus Barreirinhas and tabulation of information from this study. With the research it was found that educators who teach the curricular components of the Biological Sciences Degree Course at Campus Barreirinhas, have a notion of what ICTs are, to the point of using and recommending the use of these to other teachers of Brazilian educational institutions . Thus, it is understood that there is a need for research on the subject in question, considering that it can contribute to the dissemination of ideas and practices that strengthen the performance of education professionals, in addition to corroborating the prospect of improving student participation. , in overcoming practices considered “boring and boring” and favoring didactic aspects and the application of active strategies.